Apical sealing ability of MTA in different liquid to powder ratios and packing methods - Arash Shahravan; Masoumeh Sadeghi; Gholamhosein Eliasifar; Amir Reza Ghassemi; Ehsan Oraie (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
Introduction: In apical surgery, after apicoectomy and retro-preparation of canal, a retrofil material is applied to seal the apical region of the root canal. Mineral trioxide aggregate (MTA) is the gold standard material for this purpose. Changing water/powder ratios of MTA affects its properties. The purpose of this in vitro study was to determine the effect of liquid/powder ratio of retrofil MTA on apical dye leakage, and also compare two packing techniques for MTA. Materials and Methods: In this in vitro study, 126 intact single-root extracted teeth were instrumented using step-back technique, and obturated with lateral condensation method. The apical 3 mm of roots was resected, and retrograde preparation was performed by an ultrasonic device. Specimens were randomly assigned to 6 groups of 20 each and 6 teeth served as positive and negative controls. All teeth were retrofilled with White ProRoot MTA. Three groups were retrofilled with 0.28, 0.33, and 0.40 water/powder ratios of MTA and packed with plugger; the other three groups were retrofilled with 0.28, 0.33, and 0.40 water/powder ratios and packed with wet-cotton. Linear dye leakage was used to check apical sealing ability, and data were statistically analyzed using Kruskal-Wallis test. Results: In 0.40 liquid/powder ratio the best applicator for packing MTA was plugger. In 0.28 liquid/powder ratio, moist cotton pellet was the best applicator; in 0.33 liquid/powder ratio, there was no significant difference between the two techniques. Conclusion: Under the condition of this in vitro study, packing with moist cotton pellet in lower liquid/powder ratios of MTA, as well as packing with a plugger in higher liquid/powder ration decreased apical dye leakage.